E.E. Aylesworth, Compiled Ordinances of the City of Council Bluffs 175 (1880) - (:unkn) unknown (My University, 1880)
§ 16: Prohibited discharge of any cannon, gun, pistol, or other firearms across any street or public place without a permit from the mayor. Violators fined not less than three nor more than thirty dollars.
Keywords: DISCHARGE